At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Certainly! Let's solve the given system of linear equations step-by-step:
[tex]\[ \begin{cases} 2x + 3y = 5 \\ 2x - y = -7 \end{cases} \][/tex]
### Step 1: Express [tex]\( y \)[/tex] from the second equation.
First, we solve the second equation for [tex]\( y \)[/tex]:
[tex]\[ 2x - y = -7 \][/tex]
Rearrange to solve for [tex]\( y \)[/tex]:
[tex]\[ -y = -7 - 2x \][/tex]
Multiply by [tex]\(-1\)[/tex] to isolate [tex]\( y \)[/tex]:
[tex]\[ y = 7 + 2x \][/tex]
### Step 2: Substitute [tex]\( y \)[/tex] into the first equation.
Now we substitute [tex]\( y = 7 + 2x \)[/tex] into the first equation:
[tex]\[ 2x + 3(7 + 2x) = 5 \][/tex]
### Step 3: Solve for [tex]\( x \)[/tex].
Distribute the 3 in the equation:
[tex]\[ 2x + 21 + 6x = 5 \][/tex]
Combine like terms:
[tex]\[ 8x + 21 = 5 \][/tex]
Subtract 21 from both sides:
[tex]\[ 8x = 5 - 21 \][/tex]
[tex]\[ 8x = -16 \][/tex]
Divide by 8:
[tex]\[ x = -2 \][/tex]
### Step 4: Solve for [tex]\( y \)[/tex].
Substitute [tex]\( x = -2 \)[/tex] back into the equation for [tex]\( y \)[/tex]:
[tex]\[ y = 7 + 2(-2) \][/tex]
Simplify:
[tex]\[ y = 7 - 4 \][/tex]
[tex]\[ y = 3 \][/tex]
### Solution
The solution to the system of equations is:
[tex]\[ (x, y) = (-2, 3) \][/tex]
[tex]\[ \begin{cases} 2x + 3y = 5 \\ 2x - y = -7 \end{cases} \][/tex]
### Step 1: Express [tex]\( y \)[/tex] from the second equation.
First, we solve the second equation for [tex]\( y \)[/tex]:
[tex]\[ 2x - y = -7 \][/tex]
Rearrange to solve for [tex]\( y \)[/tex]:
[tex]\[ -y = -7 - 2x \][/tex]
Multiply by [tex]\(-1\)[/tex] to isolate [tex]\( y \)[/tex]:
[tex]\[ y = 7 + 2x \][/tex]
### Step 2: Substitute [tex]\( y \)[/tex] into the first equation.
Now we substitute [tex]\( y = 7 + 2x \)[/tex] into the first equation:
[tex]\[ 2x + 3(7 + 2x) = 5 \][/tex]
### Step 3: Solve for [tex]\( x \)[/tex].
Distribute the 3 in the equation:
[tex]\[ 2x + 21 + 6x = 5 \][/tex]
Combine like terms:
[tex]\[ 8x + 21 = 5 \][/tex]
Subtract 21 from both sides:
[tex]\[ 8x = 5 - 21 \][/tex]
[tex]\[ 8x = -16 \][/tex]
Divide by 8:
[tex]\[ x = -2 \][/tex]
### Step 4: Solve for [tex]\( y \)[/tex].
Substitute [tex]\( x = -2 \)[/tex] back into the equation for [tex]\( y \)[/tex]:
[tex]\[ y = 7 + 2(-2) \][/tex]
Simplify:
[tex]\[ y = 7 - 4 \][/tex]
[tex]\[ y = 3 \][/tex]
### Solution
The solution to the system of equations is:
[tex]\[ (x, y) = (-2, 3) \][/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.